Astrocytes Pathology in ALS: A Potential Therapeutic Target? - Johann, Sonja (Current Pharmaceutical Design, 2017)
The mechanisms underlying neurodegeneration in amyotrophic lateral sclerosis (ALS) are multifactorial and include genetic and environmental factors. Nowadays, it is well accepted that neuronal loss is driven by non-cell autonomous toxicity. Non-neuronal cells, such as astrocytes, have been described to significantly contribute to motoneuron cell death and disease progression in cell culture experiments and animal models of ALS. Astrocytes are essential for neuronal survival and function by regulating neurotransmitter and ion homeostasis, immune response, blood flow and glucose uptake, antioxidant defence and growth factor release. Based on their significant functions in “housekeeping” the central nervous system (CNS), they are no longer thought to be passive bystanders but rather contributors to ALS pathogenesis. Findings from animal models have broadened our knowledge about different pathomechanisms in ALS, but therapeutic approaches to impede disease progression failed. So far, there is no cure for ALS and effective medication to slow down disease progression is limited. Targeting only a single aspect of this multifactorial disease may exhibit therapeutic limitations. Hence, novel cellular targets must be defined and new pharmaceutical strategies, such as combinatorial drug therapies are urgently needed. The present review discusses the physiological role of astrocytes and current hypotheses of astrocyte pathology in ALS. Furthermore, recent investigation of potential drug candidates in astrocyte cell culture systems and animal models, as well as data obtained from clinical trials, will be addressed. The central role of astrocytes in ALS pathogenesis makes them a promising target for pharmaceutical interventions.
Keywords: ALS